2022
DOI: 10.1088/2053-1591/ac3f60
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yield optimization of carbon dots using response surface methodology and its application as control of Fe3+ion levels in drinking water

Abstract: Early detection of heavy metals in drinking water is a fundamental step that must be taken to prevent adverse effects on health. This research aims to develop a heavy metal ion detector by utilizing the fluorescence properties of carbon dots. Cdots were synthesized using the microwave irradiation method based on the central composite design: urea mass 0.31-3.68 gr; reactor power 200-1000 W; synthesis time is 13-46 min, and the response is quantum yield. Material characterization includes PL, TEM, UV-VIS, XRD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…The quantum yield of these C-dots was gauged against quinine sulfate (used as a reference with an excitation wavelength of 410 nm). 25 Boasting a fluorescence quantum yield of 12.5%, these C-dots either matched or surpassed the yields of some previously documented C-dots.…”
Section: Resultssupporting
confidence: 50%
“…The quantum yield of these C-dots was gauged against quinine sulfate (used as a reference with an excitation wavelength of 410 nm). 25 Boasting a fluorescence quantum yield of 12.5%, these C-dots either matched or surpassed the yields of some previously documented C-dots.…”
Section: Resultssupporting
confidence: 50%
“…Previous studies have demonstrated a close correlation between quantum dots' antioxidant properties, iron-chelating ability, their sp²-hybridized carbon cluster structure, and surface functional groups such as hydroxyl, carbonyl, and amino groups [11][12][13]. We detailedly characterized the surface functional groups and elemental composition of ginsenoside Rb1 and RBCQDs using fourier-transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS).…”
Section: Clearance Of Oxygen Free Radicals and Iron Ions By Rbcqds In...mentioning
confidence: 98%
“…The addition of metal ions to the SQDs causes the formation of a non-fluorescent complex between SQDs and metal ions. 78 The quantum yield of the SQDs reflects that these non-fluorescent complexes grow as the metal ion concentration rises and that the fluorescence emission at the maximal excitation wavelength gradually decreases. Even the TRPL measurements support the static mechanism, i.e., the complex formation between the metal ions and SQDs.…”
Section: àmentioning
confidence: 99%